Pre- and post-diagnosis dietary total antioxidant capacity and overall survival in patients with ovarian cancer: a prospective cohort study - Dong-Hui Huang; Lei Wang; Xiao-Ying Li; Ying Qin; Fang-Hua Liu; Yi-Zi Li; He-Li Xu; Fan Cao; Lang Wu; Yi-Fan Wei; Song Gao; Ting-Ting Gong; et al. (Nutrition Journal)
Abstract Background The current study aims to investigate the association between dietary total antioxidant capacity (DTAC) and overall survival (OS) in patients with ovarian cancer (OC). Methods A validated 111-item food frequency questionnaire was used to assess their pre- and post-diagnosis dietary intake. DTAC is represented by ferric-reducing ability of plasma (FRAP), total oxygen radical absorbance capacity (TORAC), hydrophilic oxygen radical absorbance capacity (HORAC), lipophilic oxygen radical absorbance capacity (LORAC), and total phenolics (TP). The OS was determined by both passive and active follow-up. Results A total of 531 patients with OC was involved in this study. High post-diagnosis FRAP (HRT3 vs. T1=0.65, 95%CI = 0.42–0.99), post-diagnosis TORAC (HRT3 vs. T1=0.68, 95%CI = 0.47–0.98), and pre-diagnosis LORAC (HRT3 vs. T1=0.62, 95%CI = 0.43–0.89) had statistically significant association with an improved OS. Additionally, increased DTAC consumption (FRAP: HR Low−Medium=0.53, 95%CI = 0.30–0.95; FRAP: HR Low−High=0.46, 95%CI = 0.23–0.93; LORAC: HR Medium−High=0.50, 95%CI = 0.27–0.91), as well as maintaining high or medium DTAC consumption (TORAC: HR Medium−Medium=0.46, 95%CI = 0.26–0.83; TORAC: HR High−High=0.57, 95%CI = 0.34–0.96; LORAC: HR High−Medium=0.43, 95%CI = 0.23–0.82), improved the OS in patients with OC. Conclusions Increased pre- and post-diagnosis DTAC intake, and maintaining moderate or high DTAC intake after diagnosis, may be associated with enhanced OS in patients with OC.